Market promotion of paid socket: A feasiblility analysis - Shu Ling Lin; Jun Lu; Tung-lai Hu; Ya-ting Huang (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
This study analyzed an innovation product i.e. paid socket, not on the market yet, and aimed at the feasibility analysis of paid socket market. We used survey method to investigate the end users. Firstly, in view of the "public", we surveyed people about what factors affecting the consumers' willingness to use this socket. The Second part was to understand merchants' ideas about the socket by in-depth interviews. Through SEM analysis, we found that safety and environmental friendliness are two important factors for the users to use the socket, and through in-depth interviews, we found the "installation convenience" and "marketing activities" are most considered by the stores. The implication of the results show that business opportunities behind the paid socket are large, whether in public area or stores , and the viewpoints of using the paid socket were different. Enhanced design and development of the socket could solve the two sides' problems and meet needs of the public and merchants by recovering the cost and expending marketing spots. Consumers didn't have to spend a lot of money to enjoy convenience, fairness and justice caused by paid sockets.
Keywords: M31; O14; 330; Paid Socket; market promotion; feasibility; competitive strategy; SEM